Émile Guimet et la morsure du canard égyptien. Un curieux au musée de Boulaq - Thomas Lebée (Les Cahiers de l'École du Louvre)
The visits of Émile Guimet (1836–1918) to the Musée de Boulaq in 1865–66 had a determining impact on his vocation as a collector and the creation, a few years later, of his museum of the study of religions (opened in Lyon in 1879 and transferred to Paris in 1889). Thanks to his testimony, the context and modes of these visits, part of the beginnings of regular organised tours in Egypt can be examined. The Lyon orientalist thus also became aware of the innovative way Auguste Mariette (1821–1881) made his Egyptological collections accessible.